2018
DOI: 10.1186/s12884-018-2122-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of behavioral risk factors of cardiovascular diseases and associated socio-economic factors among pregnant women in a rural area in Southern Nepal

Abstract: BackgroundCardiovascular diseases (CVDs) have dramatically infiltrated populations living in abject poverty in Low- and Middle-income Countries (LMICs), and poor maternal and child health outcomes have been frequently reported for those with CVD risk factors. However, few studies have explored the behavioral risk factors of CVDs among pregnant women in rural settings. This study aimed at determining the prevalence and identifying the socio-economic predictors of behavioral risk factors of CVDs among pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The most common cardiovascular lifestyle risk factor in pregnant women is physical inactivity, with a prevalence of 79.5%, which is higher than the prevalence reported in a survey of risk factors for non-communicable diseases in the general population in Burkina Faso (70.7%) [10]. Paudel et al, in a community-based cross-sectional study of 426 participants conducted in Nepal in 2018, showed a prevalence of 53.9% [20]. This may be explained by the general belief among the population (promoted by some local healthcare providers) that physical activity leads to undesirable pregnancy outcomes such as miscarriage, poor fetal growth, or premature delivery [30][31][32].…”
Section: High Prevalence Of Inadequate Physical Activity and Insuffic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cardiovascular lifestyle risk factor in pregnant women is physical inactivity, with a prevalence of 79.5%, which is higher than the prevalence reported in a survey of risk factors for non-communicable diseases in the general population in Burkina Faso (70.7%) [10]. Paudel et al, in a community-based cross-sectional study of 426 participants conducted in Nepal in 2018, showed a prevalence of 53.9% [20]. This may be explained by the general belief among the population (promoted by some local healthcare providers) that physical activity leads to undesirable pregnancy outcomes such as miscarriage, poor fetal growth, or premature delivery [30][31][32].…”
Section: High Prevalence Of Inadequate Physical Activity and Insuffic...mentioning
confidence: 99%
“…Five studies examined the risk factors for cardiovascular disease during pregnancy, such as smoking, alcohol consumption, low fruit, and vegetable consumption, daily salt intake, overweight or obesity, and hypertension [11,[15][16][17][18]. However, few studies have identified the predictors of cardiovascular lifestyle risk factors in pregnancy [20,21]. Therefore, this study aimed to determine the prevalence of, and factors associated with cardiovascular lifestyle risk factors in pregnant women in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recommendations, most pregnant women in many countries are physically inactive [17][18][19][20][21][22], and the inactivity increases as the pregnancy progresses [23,24]. Culture and cultural beliefs, misconceptions play a major role in the attitude towards exercise during pregnancy [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) include disorders of heart and blood vessels, and are usually associated with atherosclerosis, heart attacks, strokes, valvular diseases, congenital heart diseases and arrhythmia [1]. Mortality resulting from CVDs reached 17.7 million globally in 2015, which represented 31% of all global deaths.…”
Section: Introductionmentioning
confidence: 99%